Interannual Variability of Dinophysis acuminata and Protoceratium reticulatum in a Chilean Fjord: Insights from the Realized Niche Analysis - Alves-de-Souza, Catharina (Toxins (Basel), 2019)
Here, we present the interannual distribution of Dinophysis acuminata and Protoceratium reticulatum over a 10-year period in the Reloncaví Fjord, a highly stratified fjord in southern Chile. A realized subniche approach based on the Within Outlying Mean Index (WitOMI) was used to decompose the species’ realized niche into realized subniches (found within subsets of environmental conditions). The interannual distribution of both D. acuminata and P. reticulatum summer blooms was strongly influenced by climatological regional events, i.e., El Niño Southern Oscillation (ENSO) and the Southern Annual Mode (SAM). The two species showed distinct niche preferences, with blooms of D. acuminata occurring under La Niña conditions (cold years) and low river streamflow whereas P. reticulatum blooms were observed in years of El Niño conditions and positive SAM phase. The biological constraint exerted on the species was further estimated based on the difference between the existing fundamental subniche and the realized subniche. The observed patterns suggested that D. acuminata was subject to strong biological constraint during the studied period, probably as a result of low cell densities of its putative prey (the mixotrophic ciliate Mesodinium cf. rubrum) usually observed in the studied area.